PROSES KREATIF PENCIPTAAN TARI AMBREG KARYA KOREOGRAFER BATHARA SAVERIGADI DEWANDORO - Siregar, Malik; Ida Bagus Ketut Sudiasa; Nursilah (Program Studi Pendidikan Tari FBS UNJ, 2025)
This research is grounded in the importance of understanding the creative process of choreographers in developing dance works. The study aims to: (1) background of Bathara Saverigadi Dewandoro, (2) explain the structure and characteristics of the Ambreg dance, and (3) analyze the creative process involved in its creation. A qualitative approach with a phenomenological method was employed, using interviews, observations, and documentation as data collection techniques. Bathara Saverigadi Dewandoro, who comes from a Javanese cultural background, began exploring Betawi dance in 2016 as part of his search for artistic identity. Although not ethnically Betawi, he created the Ambreg dance as a reinterpretation of Betawi movement, offering a fresh perspective on its form and dynamics. Out of the 81 choreographic works he has produced, Ambreg stands out as a significant piece that led Jakarta Province to win first place in the national FLS2N competition. Bathara's creative process is analyzed using Peter Abbs' theory, which includes five stages: creative impulse, working with the medium, realization of final form, presentation/performance, and response and evaluation. Although Bathara does not rigidly follow this framework, his personal approach enriches the creative process and offers a new perspective in developing contemporary Betawi dance. These findings are expected to serve as a valuable reference for choreographers, dancers, and dance educators. Keywords: creative process, choreographer, AmbregDance, Sanggar Swargaloka.